Behaviour of primary incisor caries: a micromechanical study - E. K. MAHONEY, N. M. KILPATRICK, & M. V. SWAIN (Paediatric Dentistry, 2006)
To date, there has been no attempt to assess the mechanical properties of the entirety of a smoothsurface carious lesion in primary teeth, despite the fact that these lesions are not only common, but clinically challenging.